New Opportunities for Producers of geranium essence - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Essence of geranium, which is produced by distilling Pelargonium leaves, is used in the perfume industry. The essence is bought by the United States and Western European countries, chiefly France and the United Kingdom. During the seventies China...